An empirical approach for predicting burden velocities in rock blasting - Zhang, Zong-Xian; Chi, Li-Yuan; Yi, Changping (Journal of Rock Mechanics and Geotechnical Engineering, 2021)
An analytical relation between burden velocity and ratio of burden to blasthole diameter is developed in this paper. This relation is found to be consistent with the measured burden velocities of all 37 full-scale blasts found from published articles. These blasts include single-hole blasts, multi-hole blasts, and simultaneously-initiated blasts with various borehole diameters such as 64 mm, 76 mm, 92 mm, 115 mm, 142 mm and 310 mm. All boreholes were fully charged. The agreement between measured and calculated burden velocities demonstrates that this relation can be used to predict the burden velocity of a wide range of full-scale blast with fully-coupled explosive charge and help to determine a correct delay time between adjacent holes or rows in various full-scale blasts involved in tunnelling (or drifting), surface and underground mining production blasts and underground opening slot blasts. In addition, this theoretical relation is found to agree with the measured burden velocities of 9 laboratory small-scale blasts to a certain extent. To predict the burden velocity of a small-scale blast, a further study or modification to the relation is necessary by using more small-scale blasts in the future.